The Influence of Age on Fatal Work Accidents and Lost Days in Chile Between 2015 and 2019 - Duarte-Anselmi, G (Elsevier B.V., 2022)
The workforce ageing and the relationship between workers’ age and work accidents are factors of great concern worldwide. The aim of this article is twofold: to explore the association between workers’ age and work accidents registered by one mutual insurance company between 2015 and 2019; and to analyze the odds ratio (OR) trend of fatal accidents and accidents causing lost workdays over the same period. The odds for fatal accidents and for accidents causing lost workdays were calculated for younger and older workers through a logistic regression stratified by gender. The Prais-Winsten regression was used to evaluate the OR evolution trend in the study period. During 2015–2019, a total of 625,050 work accidents were registered. Workers aged between 45 and 99 years old in the event of a work accident are more likely to die (OR = 1.92) and be temporarily disabled (OR = 1.21) than workers aged between 18 and 44 years. In the comparison between workers aged 18–29 and 60–99, the OR for the latter increases up to 3.43 in the case of death in a work-related accident, and to 1.46 for temporary disability. Older workers are more likely to have fatal and disabling accidents than younger workers and the accidents are associated with higher costs. Furthermore, during the analyzed period, the observed OR trend was stable. Therefore, we conclude that strategic actions are needed to decrease the observed trends. © 2021 Elsevier Ltd